Exploring KSSR creative teaching strategies among Malaysian ESL teachers / Alissa Roslan - Roslan, Alissa (2013)
Creativity has been a long-debated topic of discussion when it comes to its role in education. In accordance to that, the Malaysian government has made changes to the school syllabus, starting with the primary school syllabus, also known as KSSR (Primary School Standard Curriculum). In their approach to have the schools to be less exam-oriented with the inclusion of school-based assessment, KSSR has also noted the importance of creativity in its syllabus. However, despite this new approach, there are still some issues faced by Malaysian ESL teachers that have not been dealt with. If this remains, then one would wonder how creativity will be implemented in the classroom amidst these issues. As such, this study was made to investigate the teachers’ challenges and their creative teaching strategies, and later on, to make recommendations based on the challenges and strategies they used. The study was meant to bridge the gap between the issues faced by teachers and the demands of the new syllabus, KSSR. This is a case study, focusing on two ESL teachers who have been involved in the syllabus change and have had experience in teaching KSSR since its first implementation. In this study, several important pointers were found, some of which had made the teachers source out their lessons on their own and having to follow certain procedures in the planning of their lessons. But all seem to be leading to one conclusion; time. The results, though pointing at the issue of time, seemed to have been stemmed from many places. Despite being from many types of issues, it still leads back to the issue of time.